Cross-sectional study of the anthropometric characteristics of children with congenital Zika syndrome up to 12 months of life - Rita de Cássia Oliveira de Carvalho-Sauer; Maria da Conceição Nascimento Costa; Enny S. Paixão; Natanael de Jesus Silva; Florisneide Rodrigues Barreto; Maria Gloria Teixeira (BMC, 2020)
Abstract Background Little is known about physical development of children with Congenital Zika Syndrome (CZS). This study aims to evaluate the anthropometric characteristics of children with CZS up to 12 months. Methods This is a cross-sectional study developed with 46 children with CZS living in Bahia. We used the Public Health Events Register, Live Births Information System and Childcare Records of Primary Health Care Services. Descriptive analysis was performed by distributing absolute and relative frequencies and median and interquartile range. The Weight/Age (W/A), Length/Age (L/A), Weight/Length (W/L) and Head Circumference/Age (HC/A) indexes were calculated for each month and expressed in z-score values, and the results were evaluated individually and by group average. Values between ≥ − 2 and ≤ 2 standard deviations were used as reference. T-Student and Spearman's Correlation Tests were applied to verify the existence of any relationship between maternal and children's variables with the anthropometric indexes weight/age and height/age at birth and at 3, 6 and 12 months of age. Results The studied children had high proportions of low birth weight (23.9%), dysphagia (56.8%) and seizures (53.5%). The mean z-score for the HC/A index at birth was − 3.20 and remained below − 3 z-scores throughout the assessed period. The analysis of the indices equivalent to every single child's anthropometric measurement showed a deficit in 20.4% of the W/A, 39.1% of the L/A, 9.2% of the W/L and 85.7% of the HC/A measurements. Distribution of the mean values of these anthropometric indices revealed a risk of delayed stature growth (L/A < -1 z-score). There was a statistically significant association between L/A at 12 months and dysphagia (p = 0.0148) and a positive correlation between breastfeeding time and W/A. No statistically significant correlation was found between any other tested variables. Conclusions We observed a deficit in the HC/A index, which is a common feature in CZS, but also a high proportion of W/A and L/A deficit. The average group z-score highlighted the risk of delay in stature growth for age, which calls attention to the need for health interventions, as this condition exposes them to a higher risk of morbidity and mortality.